Education, Sexuality and Anti-gender Movements in Latin America - Anelise Gregis Estivalet; Gabriel Dvoskin (Gender a Výzkum, 2022)
This article analyses the discourses of anti-gender movements circulating in Brazil and Argentina. The aim of our research is to determine the regularities and specificities of these movements. Specifically, it analyses the representations that are mobilised in the political sphere about gender and sexuality and the role that is attributed to the school institution in these matters. Therefore, an analysis is made of the discussion relating to legislative bills and the parliamentary debates that took place on the Escola Sem Partido (ESP) in Brazil between 2014 and 2017 and on the Interrupción Voluntaria del Embarazo (IVE) in Argentina in 2018. The focus here is exclusively on the discourse employed in favour of the ESP project in Brazil and against the IVE in Argentina, since the ESP and the IVE are opposed to the expansion of rights relating to gender and sexuality. Finally, we concluded that the anti-gender discourse in these countries shares with the religious discourse its precepts relating to gender and sexuality issues. However, the current discourse of this movement is not positioned grounded in religious discourse. Instead, it appeals to scientific and legal discourses as a mechanism of establishing legitimacy and as a way of attracting a wider audience.